Production and characterization of metallurgical coke from duduguru coal - M. Baba, Nasirudeen; Zubairu, Yusuf; C. Onwuka, Jude; A. Ambi, Ahmad (International Journal of Advanced Chemistry, 2021)
This work illustrates the production and characterization of metallurgical coke from Duduguru coal, Obi local Government Area of Nasarawa State, Nigeria. The analytical assessment of properties such as proximate analysis, elemental composition, and calorific value are very important to know the coking qualities of the coal. The proximate analysis showed that the moisture content, ash content, volatile matter, fixed carbon and calorific values of the coal are; 1.86%, 18.82%, 43.74%, 53.58% and 5405.15 Cal/g respectively. Based on the result of the proximate analysis, the coal is of good metallurgical coke quality from an industrial prospective and heat generation is to be considered. Elemental analysis shows that due to the low heavy metals, low sulfur content and ash content of the coal, utilization of the coal within a safe environment is feasible with just a little environment impact and make it suitable for blending with strong coking or caking properties.Â Â